DD-026 New market for medicines: Do the suppliers meet their commitments?. (14th February 2016) - Kamel, A Bel; Derain, L; Bellossi, F; Locher, F; Meunier, A
Abstract : Background: Purchasing procedures in hospital are subject to the public procurement code and vary with the amounts of the purchase. The tender must be implemented when the purchase amount exceeds 200 000 Euros HT during the contract period. Although suppliers tender on estimated quantities, sometimes laboratories do not fulfil the first orders. Purpose: The objective of this study was to analyse the proportion of new markets whose orders were not honoured in the first 3 months after the beginning of the market. Material and methods: The study focused on the local tender for generics starting in July 2015. The number of molecules for which the suppliers changed compared with the previous market were listed. The number of molecules for which the orders were not met by the contract holders in the first 3 months were also listed. Then we analysed the causes of these stock shortages. We also recorded if the upholder of the market was the best bidder or not, and if the previous market was subject to drug shortages or not. Results: The local market included 111 market changes. The proportion of new markets whose orders were not honoured in the first 3 months was 10%. 82% of these stock-outs concerned generics. 5 different suppliers were concerned, including 4 generic manufacturers. In 82% of cases, the successful supplier was the best bidder. 4 different causes of drug shortages were reported, the most common was a problem of quality control of raw material. In 18% of cases. the previous market was also subject to stock-outs. Conclusion: Drug shortages on new markets are significant, and they may impact on quality of patient care and are time consuming for teams managing stock-outs (calls to other suppliers, orders, etc). It would be interesting to quantify the management cost of a drug shortage (human time, financial cost) and to establish indicators for the performance of suppliers that could help in the choice of future tenders. References and/or Acknowledgements: Directive 2004/18/EC of the European Parliament and of the Council of 31/03/2004 on the coordination of procedures for the award of public contracts. No conflict of interest.